1. THE PROBLEM
Take the definition of the derivative:
$$\frac{d}{dx}f(x)=\lim_{h\to 0}\frac{f(x+h)-f(x)}{h}$$
Using this definition to calculate the derivative of $e^x$ is not the most trivial thing to do, as one ends up with:
$$\frac{d}{dx}e^x=e^x\lim_{h\to 0}\frac{e^h-1}{h}$$
We can finish this off by a change of variables $n=\frac1h$.
$$e^x\lim_{h\to 0}\frac{e^h-1}{h}=e^x\lim_{n\to\infty}n(e^{1/n}-1)=e^x\cdot\ln e=e^x$$ Note: the second to last equality holds because of a limit definition of the natural logarithm: $\ln x=\lim_{n\to\infty}n(x^{1/n}-1)$.
As we see, calculating the derivative of the exponential function is not easy with the usual limit definition of the derivative. It requires calculating a limit that is not obvious without knowing a special limit definition of $\ln x$.
One can wonder then, are there easier ways of proving that $\frac{d}{dx}e^x=e^x$? Indeed, there are easier ways to prove this. But all of the proofs I have ever seen either assume a taylor series or limit definition of the exponential function, or somehow use the derivative of $\ln x$ which itself has similar calculation problems. Finally, the proofs lack deep motivated intuition, and are raw algebraic manipulations for the most part. They prove things well, but they don't explain things well.
Question: is there a way to find the derivative of the exponential function intuitively?
2. POSSIBLE SOLUTIONS
I didn't ask this question without giving it a little thought.
Path A
I figured that one solution to this problem might be by intuituvely explaining how in the world $\ln x$ is equal to $\lim_{n\to\infty}n(x^{1/n}-1)$.
Euler observed, quite unrigorously, that if $\epsilon$ is an arbitrarily small number, then:
$$\ln(1+\epsilon)=\epsilon$$
Similarly, if we let $n$ be an arbitrarily large number, we can observe that:
$$x^{1/n}-1=\epsilon$$
Plugging this observation into the first one, we have:
$$\ln(x^{1/n})=x^{1/n}-1$$ $$\frac1n\ln x=x^{1/n}-1$$ $$\ln x=n(x^{1/n}-1)$$
Thus:
$$\ln x=\lim_{n\to\infty}n(x^{1/n}-1)$$
This would almost work as a solution, except for the fact that here we make observations that work for logarithms of all bases. The observation $\log_b(1+\epsilon)=\epsilon$ is valid for all bases $b$. The second observation we made doesn't even relate specifically to logarithms. Thus, the "intuition" in this case assumes that the limit can be equal to a logarithm of any base. This is obviously false; computations evidently show that this limit holds only for $b=e$. And it is not evident at all why it has to be $e$ and nothing else.
This solution will be complete if it can be shown why base $e$ and none other work.
Path B
Another solution to this problem would be noting that the exponential function grows proportionally to its size. The problem with this intuition is that it is not at all evident why would this function follow such a behavior.
The mystery is, how does one start with simple algebraic properties of exponents, which are trivially defined by multiplication, and arrive the conclusion that this function follows its unique growth behavior. It might help to note that exponentiation turns an arithmetic sequence into a geometric sequence.
Id est, if:
$$\alpha_n=a+\sum^n_1 d$$ $$\gamma_n=b\prod^n_1 r$$
Then:
$$e^{\alpha_n}=e^{a+\sum^n_1 d}=e^a\prod^n_1 e^d=b\prod^n_1 r=\gamma_n$$
If there is a way to start with basic algebraic facts about exponents and end up (intuitively) with the fact that exponential growth is proportional to its size, we could then justify the fact that $e^x$ is the solution of $y'=y$, $y(0)=1$. From there, we could automatically say that the derivative of the natural exponential is itself.
Caveat: While solving this ODE, there is still a problem because we need to compute the integral of $\frac1x$. It turns out that we can intuitively solve this task. We can begin by splitting the area under the curve into n rectangles of equal area $A$, situated between corresponding x coordinates: $\{x_0, x_1, ..., x_n\}$. We will then note that:
$$A=y_0(x_1-x_0)=y_1(x_2-x_1)$$ $$\frac{x_1-x_0}{x_0}=\frac{x_2-x_1}{x_1}$$ $$\frac{x_1}{x_0}-1=\frac{x_2}{x_1}-1$$ $$\frac{x_1}{x_0}=\frac{x_2}{x_1}$$
This will generalize to $\frac{x_n}{x_{n-1}}=\frac{x_{n+1}}{x_n}$. What this means is that, if rectangles are the same area, if we increase the x coordinates geometrically (because the ratio between next and current x coordinate is constant), we increase the area arithmetically. This is precisely what logarithms do, they turn geometric sequences into arithmetic sequences (opposite of the exponentials). Thus, the integral of $\frac1x$ will be some kind of logarithm.
The missing bit here, again, is...why is it base e, and not some another base?
Other paths
Those two paths are most likely not the only approaches.
3. MOTIVATION
At this point, I overstressed the word "intuition", and I just wanted to explain myself. I just really love to explore things that are proven symbolically, in a natural way. I might be considered weird for trying to do that so deeply for such a simple derivative, but oh well.
Thank you in advance for any good insights into this problem.